Job Stress on Certified Teachers at Madrasah Aliyah Negeri Y Padang City - Fitria Rahmi; Raudhatul Husni; Rani Armalita (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2021)
This study aims to look at the description of work stress on certified teachers at Madrasah Aliyah Negeri (MAN) Y Padang City. Respondents in this study were certified teachers at MAN Y Padang City. The sampling technique used is saturated sampling as many as 66 certified teachers. The measuring instrument used in this study was made by the researcher himself referring to the measuring instrument made by Triana (2015) based on the work stress theory of Beehr and Newman (1978). The research method used is descriptive quantitative. Based on the research results obtained, certified teachers at MAN Y Padang City have low work stress. In addition, a significant difference in work stress was found by gender. Where female certified teachers have a higher level of work stress than male certified teachers.